Patterns and wavelet coherence analysis of tidal dynamics and chlorophyll a concentration - M.N. Hidayat; R. Wafdan; M. Ramli; Z.A. Muchlisin; S. Rizal (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Understanding the correlation between tidal rhythms and marine organism behavior is crucial. This extends beyond fluctuations in chlorophyll a concentrations and includes various biological processes in the marine environment. Awareness is key for a comprehensive perspective on the role of tidal forces, affecting ocean’s physical aspects and life form diversity. This study aims to explore the complex relationship between tidal movements and chlorophyll a concentrations in the northern Bay of Bengal, focusing on how tidal rhythms affect chlorophyll a concentrations.METHODS: The analyzed variables include tidal parameters, such as lunar semidiurnal tidal characteristics and Simpson–Hunter parameters, as well as sea level, tidal current, and current magnitude, obtained from the tidal model driver. Additionally, hourly chlorophyll a data for January 2022 were acquired from the geostationary meteorological satellite Himawari-8, and the rate of change of chlorophyll a was determined through chlorophyll a calculations. This study employs wavelet analysis, applying continuous wavelet transform and wavelet transform coherence for chlorophyll a, rate of change of chlorophyll a, sea level, tidal current, and current magnitude, to explore oscillation patterns and temporal correlations within the marine ecosystem of the northern Bay of Bengal.FINDINGS: Lunar semidiurnal tidal amplitudes increase toward the north, peaking at the Sagar and Ramree Islands, and tidal phases rise from south to northeast. Most of the bay, categorized by <0.25 Formzahl values, experiences semidiurnal tides. Surface lunar semidiurnal elliptic currents, stronger in the north and east, flow clockwise and turn counterclockwise toward the south. The Simpson–Hunter parameter indicates heightened tidal mixing, particularly along the northern and eastern coasts. Region 2 showed the highest mean chlorophyll a concentration (12.58 milligram per cubic meter), whereas Region 1 showed the lowest mean chlorophyll a concentration (0.79 milligram per cubic meter). Similar trends were observed for tidal current and current magnitude. The continuous wavelet transform analysis provides data on chlorophyll a and the rate of change of chlorophyll a within 6, 12, and 24 hour, sea level changes within 8–16 hours, and consistent tidal effects on tidal current and current magnitude in the range of 5–7 hour. The wavelet transform coherence analysis highlights the relationships between chlorophyll a and sea level over 12- and 24- hour periods and between chlorophyll a and current magnitude. Furthermore, the wavelet transform coherence analysis examines the rate of change in chlorophyll a in relation to tidal currents over 6, 12, and 24 hour.CONCLUSION: Tides remarkably affect chlorophyll a concentrations. There are strong links between chlorophyll a concentrations and key tidal aspects, such as sea level and current magnitude. Higher tidal variables correlate with increased chlorophyll a concentrations and are related to the Simpson–Hunter parameter, indicating that regions with vigorous mixing show higher chlorophyll a concentrations. This finding highlights the major role of tidal forces and variations in the chlorophyll a concentrations in the Bay of Bengal. The wavelet transform coherence analysis of chlorophyll a, sea level, and current magnitude data in Regions 1, 2, and 3 show notable coherence in all areas.